Developing Nearpod-Based Interactive Multimedia on the Topic of Indonesian Cultural Diversity for 4th Grade Elementary School Students - Alawiyah, Indi Azza; Ahmadi, Farid (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2024)
This research aims to create a valid, practical, and effective Nearpod-based interactive learning media to improve learning outcomes of social sciences content on the material